Interferon-γ production in response to the cytotoxic T lymphocyte epitope within an antigen incorporated in simian virus 40 virus-like particles - Takeharu Watanabe; Masayuki Hayashi; Masaaki Arai; Sho Matsushita; Hiroshi Handa; Masaaki Kawano (Heliyon)
In a previous study, we showed that administration of antigen-incorporated virus-like particles (VLPs) derived from simian virus 40 (SV40) induces production of cytotoxic T lymphocytes (CTL), as well as antibodies against the incorporated antigen(s), without the need for an adjuvant; however, it remains unclear how immune cells recognize and respond to the SV40 capsid because SV40 VLPs did not upregulate expression of maturation markers on dendritic cells. In this study, administration of chicken ovalbumin (OVA) incorporated within SV40 VLPs induced interferon (IFN)-γ production in response to the OVA CTL epitope. IFN-γ production in response to the OVA CTL epitope was not inhibited in B cell-depleted mice, but it was inhibited in cluster of differentiation (CD)4+ T cell-depleted mice. Administration of SV40 VLPs upregulated expression of CD63/CD68/CD83/CD86/CD196, and induced secretion of C-C chemokine ligand (CCL)3 and CCL4, by B cells, as well as secretion of CCL4 by T cells and tumor necrosis factor-α by bone marrow-derived dendritic cells.